The Cost of Privacy: Welfare Effects of the Disclosure of COVID-19 Cases - Argente, David; Hsieh, Chang-Tai; Lee, Munseob (The Review of Economics and Statistics, 2022)
South Korea publicly disclosed detailed location information of individuals who tested positive for COVID-19. We quantify the effect of public disclosure on the transmission of the virus and economic losses in Seoul. The change in commuting patterns due to public disclosure lowers the number of cases by 60,000 and the number of deaths by 2,000 in Seoul over two years. Compared to a city-wide lockdown that results in the same number of cases over two years as the disclosure scenario, the economic cost of such a lockdown is almost four times higher.